Learning Outcomes: How does the Experimentation of the CIRC Models? - Marsya Nada, Nabilla; Nurul Azizah; Siti Zulaikhah; Baharudin; Waluyo Erry Wahyudi (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to examine the effectiveness of the CIRC (Cooperative Integrated Reading and Composition) learning model on students' learning outcomes in Islamic Culture History (SKI) at MAN 1 Pringsewu. The research employs an experimental method with a post-test only control-group design. The sample consists of two classes: the experimental class, where the CIRC learning model is implemented, and the control class, which uses the conventional learning model. Data were collected through a post-treatment SKI test. Data analysis was conducted using a T-test to determine significant differences in the learning outcomes between students who were taught using the CIRC model and those who were not. The implications of this study suggest the need to use an interactive learning model in SKI lessons and that educators should make decisions to create flexible and adaptable teaching methods. The results of the study show a significant improvement in the learning outcomes of students using the CIRC model, particularly in material comprehension and collaborative skills. The T-test results show a Sig. (2-tailed) of 0.001 < 0.05, thus based on the decision criteria for the independent sample t-test, it can be concluded that H0 is rejected and Ha is accepted. Based on these findings, the CIRC learning model has proven to be effective in improving learning outcomes, especially in SKI at MAN 1 Pringsewu.